IMITATIONAL METHOD OF TEACHING FOR CARDIO-PULMONARY RESUSCITATION TRAINING IN MEDICAL EDUCATION - Akhmadaliev Shokhrukh Shukhratovich; Sidikov Akmal Abdikaxarovich (Journal Park Publishing, 2023)
The spread of cardiopulmonary resuscitation (CPR) skills is essential for surviving cardiac arrest. Virtual Reality (VR) pulmonary resuscitation training is the cheapest and easiest method for medical students to learn how to apply chest compressions at the right speed and depth. The study examined the compliance of cardiopulmonary resuscitation with quality criteria performed using virtual reality.
Keywords: Virtual reality, virtual patient, cardiopulmonary resuscitation.